Translation with Extrinsic Aspect Approach in the Form of Pragmatics and Modulation Translation Method - Wuri Syaputri; Akbar Fi Rizky; Widyasari Widyasari; Yudi Efendi (ELT-Lectura, 2023)
The following study aims to examine the extrinsic elements in the form of pragmatics contained in the catchphrase "my friend calls me murphy, you call me, Robocop" in the movie Robocop 3. The author believes that every expression has a hidden meaning in it. To translate a literary work such as a movie, a complete understanding is needed, especially in its linguistic elements. This information can be used in the process of translating a literary work in order to get a good, acceptable, and accurate translation. The research method used for this study is qualitative, where the author sees snippets of conversations in movie then analyzes the pragmatic elements contained therein. These elements can be in the form of speech and actions desired by the speaker. The author chose to analyze a catchphrase or conversation line in the movie because of its iconic nature and known by most connoisseurs or fans of the movie. The following study is expected to reveal the hidden meaning of a catchphrase that contains the true will of the speaker. The translation of literary works is done by modulating methods because it is in accordance with the linguistic aspects of a movie that has many points of view of each character played. The author also hopes that this study can be used as reference material for translating movie-type literary works.